Human immune system - Wobser, Alisse; Mann, David; Rodriguez, Carlo; Educational Video Network, Inc., Inc (Huntsville, Tex. : Educational Video Network, Inc., 2002)
Introduces the human immune system, different types of diseases, Koch's postulates for relating a specific pathogen to a specific disease, and the functions of the lymphatic system. Discusses the innate immune system and the adaptive immune system. Describes actions that can be taken to prevent the spread of disease
Videography, Dave Mann ... et al. ; graphics/animation, Elizabeth Sharp, Michael Griffin, Eric Peschel
Host, Constance Jones ; narrators, Judé L. Routh, Constance Jones
VHS
Keywords: Immune System -- physiology